The Existence of the Lex Certa Principle in the Construction of the Crime of Illicit Enrichment in the Criminal Law System of Timor-Leste - Aderito Antonio Pinto Tilman; I Wayan Rideng; Ni Komang Arini Styawati (Transpublika Publisher, 2026)
A core tenet of criminal law is the principle of legality, which dictates that no conduct is punishable without a pre-existing legal prohibition (nullum crimen, nulla poena sine lege). This concept, codified in Article 1(1) of the Timorese Penal Code, forms the bedrock of the nation’s legal framework, ensuring predictability in the law and the protection of fundamental human rights. With the ratification of the United Nations Convention Against Corruption/UNCAC 2003 by the Timor-Leste Government in 2009, and the National Parliament has criminalized Illicit Enrichment as a criminal act of corruption in its national law. However, in the formulation of illicit enrichment, there are norms that are unclear, vague and give rise to interpretation in law enforcement. The unclear formulation of the law, lex certa will create legal uncertainty for the community due to ambiguity. This study aims to analyze the existence of the lex certa principle in the theory of the principle of legality towards Illicit Enrichment, and how its implications in application, in order to build a strong legal system. Using a library research method, this study examines relevant legal, conceptual, and expert opinions. The results indicate that illicit enrichment cannot be implemented in Timor-Leste due to unclear, vague, and ambiguous formulations of the norm, as well as conflicts with the Timor-Leste Constitution. In conclusion, the study recommends clarifying and precisely defining illicit enrichment provisions to comply with the lex certa principle, ensuring legal certainty, effective enforcement, and alignment with constitutional norms.